Promoting oral health and entertainment for children from underprivileged communities through university extension (Research, Society and Development, 2021)
The university extension, in the dental field, is based on the provision of services to the oral health of the population, through several and significant programs. This work aims to report the experiences and activities experienced by Dentistry students at the Federal University of Campina Grande, members of the Extension Program (PROBEX): "Human Freshmen: Promoting Oral Health in Pastoral da Criança", belonging to the axis directed to actions to promote oral health with children through educational practices in communities in the city of Patos, Paraíba (PB). Children from 0 to 12 years of age participated in the actions, as well as their parents and guardians who attended the Pastoral da Criança in their communities. The Children's Axis had the participation of 8 members, namely: 1 coordinating teacher, 1 scholarship student and 6 volunteer students, who met every week to schedule and plan actions in order to disseminate knowledge about it of oral health. The program provides safe, clear and accurate information dissemination, which is suitable for children, in a playful and easy to understand way, enabling greater learning. In addition, the actions favor the process of teaching and developing the extension student, since this contact with the community allows social interaction with different people, allowing the construction of a professional trained in prevention and health promotion.